2019
DOI: 10.17140/pcsoj-5-146
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Barriers to Treating Domestic Violence for Middle Eastern Women Living in the United States

Abstract: A lthough domestic violence (DV) has been a problem throughout history, it is only in the past two decades that researchers have shown interest in analyzing how cultural values and social norms relate to aggression and violence towards women. 1 DV, as noted by Hawcroft et al 2 "includes violence perpetrated by a family member or intimate partner towards another adult. Much of the current international evidence focuses on intimate partner violence (IPV), which is a subset of domestic violence" (p. 2). The Cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 31 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…In this systematic review and meta-analysis, more than one third of the study participants were not disclosed their experience of violence. This is consistent with other similar systematic review and meta-analysis [54, 56, 57]. This high pooled prevalence of non-disclosure implies: (i) the need of strengthening women empowerment for their right, (ii) the influence of cultural belief and fear associated with domestic violence related disclosure, (iii) though the government works on women and girls’ empowerment, this study indicate the needs of evaluating its effectiveness.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this systematic review and meta-analysis, more than one third of the study participants were not disclosed their experience of violence. This is consistent with other similar systematic review and meta-analysis [54, 56, 57]. This high pooled prevalence of non-disclosure implies: (i) the need of strengthening women empowerment for their right, (ii) the influence of cultural belief and fear associated with domestic violence related disclosure, (iii) though the government works on women and girls’ empowerment, this study indicate the needs of evaluating its effectiveness.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with a recently published review from Middle East. This study revealed that fears of further violence, loss of support and relationships, cultural expectations and family reputation as reasons why women do not seek services for domestic violence [57, 58].…”
Section: Discussionmentioning
confidence: 99%
“…Patriarchal community norms around sex and reproduction also play an important role in shaping some migrant minority ethnic women's experiences of reproductive coercion and abuse and how it intersects with intimate partner violence and sexual violence. Although studies have identified many of the ways that patriarchal norms can be exploited by perpetrators in the context of minority ethnic women's experiences of intimate partner violence more generally (Raj and Silverman 2002;Maher and Segrave 2018;Do, Weiss, and Pollack 2013;Balice et al 2019), they have largely ignored the specific interaction between these norms and reproductive coercion and abuse. In particular, this study highlights how particular attitudes towards women's reproductive capacity can facilitate reproductive coercion and abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is not our intention to suggest that "culture" is a fixed or innate feature for any individual or group of individuals (AMES Australia and Australian Government Department of Social Services 2016). However, what almost all cultures have in common to a greater or lesser extent are types of patriarchal beliefs associated with violence against women (Do, Weiss and Pollack 2013;Balice et al 2019;Webster et al 2018;Fakunmoju and Bammeke 2017). These beliefs -in whatever manifestation they take in a particular community -and how they intersect with structural, societal, and relationship issues, is the focus of this paper.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation